'What are these people: migrants, immigrants, refugees?': Migration-related terminology and representations in Portuguese digital press headlines. (March 2019) - Torkington, Kate; Ribeiro, Filipa Perdigão
Abstract: There has been increasing debate in academic circles over the 'correct' labelling of different forms of migration. During the summer of 2015, the intense media focus on the so-called 'Mediterranean migrant crisis' also led to heated terminological debate in certain sections of the international press. This debate centred not only on semantic questions, but also raised ideological issues since the terminology used to describe social groups almost certainly has social implications: the discursive construction of people 'on the move' may lead not only to the formation of stereotypical social representations but also, ultimately, to different treatment of different groups of people in 'host' countries. Using a methodology which combines CDA and frame analysis, this paper seeks to explore how different migration-related terms (i.e. immigrants, migrants, refugees) were used in the headlines of the Portuguese digital press around the time of the crisis, and what kind of representations of these social actors were being (re)constructed through these texts. We conclude that although there are some similarities with the findings of other studies set in different countries, namely the impersonalization, genericization and passivation of these social actors, there are also some differences which can be attributed to the socio- political context in which the Portuguese press is embedded. As a 'peripheral' European country which felt no direct impact from the unfolding humanitarian crisis, Portugal was clearly seeking to bolster a positive self-representation as a tolerant, welcoming and inclusive society.